T1 Genetic overlap study between acute respiratory distress syndrome and idiopathic pulmonary fibrosis. (11th November 2022) - Guillen-Guio, B; Allen, RJ; Leavy, OC; Hernández-Beeftink, T; Suarez-Pajes, E; Jenkins, RG; Flores, C; Wain, LV
Abstract : Introduction and Objective: Acute respiratory distress syndrome (ARDS) is a critical lung condition induced by a systemic inflammatory response. A subset of ARDS patients can also develop pulmonary fibrosis (i.e. lung scarring). Idiopathic pulmonary fibrosis (IPF) is the most common cause of pulmonary fibrosis in the general population. Genome-wide association studies (GWAS) of IPF and post-sepsis ARDS suggest that these phenotypes could share genetic risk factors. Here we performed the first genetic overlap study between IPF and ARDS to identify shared genetic risk loci that might be informative about development of lung fibrosis after ARDS. Methods: We used summary statistics from large meta-GWASs of IPF risk (4, 125 cases, 20, 464 controls) and post-sepsis ARDS (716 cases, 4, 399 controls), as well as individual-level data from a subset of individuals from the ARDS GWAS (321 cases, 3, 249 controls). We performed polygenic risk score (PRS) analyses to assess if IPF GWAS variants could be used to predict ARDS risk. We constructed PRSs as the weighted sum of variants reaching different p -value thresholds in the IPF meta-GWAS, and tested their association with ARDS risk, whilst adjusting for age, sex and population stratification. We also assessed individual genetic signals to identify variants shared between both traits. We conducted colocalisation analyses to determine whether the same causal variant was driving both phenotypes, and studied the association of overlapping variants with gene expression. Results: The PRS calculated from IPF variants that passed the best p -value threshold (i.e. p =0.0011) predicted ARDS risk ( p =4.07x10 -04, OR[95%CI]=1.24[1.10, 1.39]). We also found that the ARDS protective allele at HLA-DQA2 was associated with IPF risk ( p =1.28x10 -04 ) and that the IPF risk allele at ATP11A conferred protection from post-sepsis ARDS ( p =0.003). The latter was associated with protection from severe COVID-19 in previous studies. Colocalisation analyses were inconclusive, likely due to the limited ARDS sample size. Conclusions: Our risk score analyses suggest that there may be shared biological processes underlying IPF and ARDS risk. However, we note opposite directions of effect on IPF and ARDS risk for some loci. Further studies are needed to assess if these results are also informative about fibrotic sequelae of ARDS. Please refer to page A208 for declarations of interest related to this abstract.